Expanding perspectives of soil nitrification to include ammonia‐oxidizing archaea and comammox bacteria. Issue 2 (17th April 2020) - Lu, Xinda; Taylor, Anne E.; Myrold, David D.; Neufeld, Josh D.
Abstract: Catalyzed by multiple groups of phylogenetically distinct microorganisms, soil nitrification impacts ground water quality, greenhouse gas emissions, and agricultural practices. This review explores known microbial players involved in nitrification, encompassing aspects of biogeography, phylogenetic diversity, physiology, and activity. We discuss distributions and activities of ammonia‐oxidizing archaea and bacteria as they relate to environmental and edaphic factors and highlight a newly discovered role for terrestrial comammox bacteria. Ecological interactions of ammonia oxidizers and nitrite oxidizers are discussed, as are their respective contributions to N2 O emissions. Given these expanding perspectives of soil nitrification, we underline the importance of combining culture‐based methods with metagenomic approaches to help address remaining knowledge gaps.